(untitled) (Marketing Journal, 2025)
This article examines mechanisms for enhancing the effectiveness of digital marketing strategies in agri -industrial enterprises. The study analyzes search engine optimization (SEO), social media marketing, content marketing, and data -driven decision -making approaches. Uzbekistanʼs agri -industrial sectorʼs digital transformation processes are assessed in the context of international experience. Empirical findings indicate that prioritizing SEO strategies ensures lower costs and higher conversion rates compar ed to social media. The research results serve to develop practical recommendations for optimizing digital marketing investments in agri - industrial enterprises. 621